Celebrity worship: friend or foe of mental health? Qualitative evidence from Ghanaian adolescents - Anthony Kwame Morgan; Daniel Katey; Bernice Wadei; David Forkuor; Charles Peprah (International Journal of Adolescence and Youth)
In an era where celebrity influence shapes the lives of young people worldwide, understanding its impact on adolescents has never been more critical. This study explores the growing phenomenon of celebrity worship among Ghanaian adolescents by employing an exploratory research design. Primary data were collected through semi-structured interviews with 12 adolescents who were conveniently sampled. Interpretative phenomenological analysis approach was adopted to uncover recurring patterns and themes in the data. Our findings show dual effects of celebrity worship on the mental health of the adolescents. These encompass positive aspects such as inspiration and motivation, and negative aspects like anxiety and low self-esteem. We also established that adolescents engage in celebrity worship for varied reasons, including a desire for social connection and a need for escapism. Thus, our study highlights the dynamic effects of celebrity worship on the mental health of adolescents. Further quantitative studies are recommended for a comprehensive understanding of this relationship.